Efficiency Optimization of a DSP-Based Standalone PV System Using Fuzzy Logic and Dual-MPPT Control - Al Nabulsi, Ahmad (2012)
This paper presents a new digital control scheme for a standalone photovoltaic (PV) system using fuzzy-logic and a dual maximum power point tracking (MPPT) controller. The first MPPT controller is an astronomical two-axis sun tracker, which is designed to track the sun over both the azimuth and elevation angles and obtain maximum solar radiation at all times. The second MPPT algorithm controls the power converter between the PV panel and the load and implements a new fuzzy-logic (FLC)-based perturb and observe (P&O) scheme to keep the system power operating point at its maximum. The FLC-MPPT is based on a voltage control approach of the power converter with a discrete PI controller to adapt the duty cycle. The input reference voltage is adaptively perturbed with variable steps until the maximum power is reached. The proposed control scheme achieves stable operation in the entire region of the PV panel and eliminates therefore the resulting oscillations around the maximum power operating point. A 150-Watt prototype system is used with two TMS320F28335 eZdsp boards to validate the proposed control scheme performance.